Determinants of electronic procurement adoption in an organization: Comparative study of private and public organization: The case of TANESCO and TBL - Mushi, Gift .O (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirement for the award of the Degree of Master of Science in Procurement and Supply Chain Management (Msc- PSCM) of Mzumbe University